A detailed study of cholinium chloride and levulinic acid deep eutectic solvent system for CO2 capture via experimental and molecular simulation approaches1. Issue 32 (28th August 2015) - Ullah, Ruh; Atilhan, Mert; Anaya, Baraa; Khraisheh, Majeda; García, Gregorio; ElKhattat, Ahmed; Tariq, Mohammad; Aparicio, Santiago
<x xml:space="preserve">Abstract</x> Choline chloride + levulinic acid deep eutectic solvent is studied as a suitable material for CO2 capturing purposes.